Automated slice‐specific simultaneous z‐shim method for reducing B1 inhomogeneity and susceptibility‐induced signal loss with parallel transmission at 3T. Issue 4 (7th October 2014) - Schneider, Rainer; Boada, Fernando; Haueisen, Jens; Pfeuffer, Josef
<x xml:space="preserve">Abstract</x> Purpose Through‐plane susceptibility‐induced signal loss in gradient recalled echo (GRE)‐based sequences can considerably impair both the clinical diagnosis and functional analysis of certain brain areas. In this work, a fully automated simultaneous z‐shim approach is proposed on the basis of parallel transmit (pTX) to reduce those signal dropouts at 3T. Theory and Methods The approach uses coil‐specific time‐delayed excitations to impose a z‐shim phase. It was extended toward B1 inhomogeneity mitigation and adequate slice‐specific signal‐dephasing cancellation on the basis of the prevailing B0 and B1 spatial information. Local signal recovery level and image quality preservation were analyzed using multi‐slice FLASH experiments in humans and compared to the standard excitation. Spatial blood‐oxygen‐level‐dependent (BOLD) activation coverage was further compared in breath‐hold functional MRI. Results The pTX z‐shim approach recovered approximately 47% of brain areas affected by signal loss in standard excitation images across all subjects. At the same time, B1 shading effects could be substantially reduced. In these areas, BOLD activation coverage could be also increased by approximately 57%. Conclusion The proposed fully automated pTX z‐shim method enables time‐efficient and robust signal recovery in GRE‐based sequences on a clinical scanner using two standard whole‐body transmit coils. Magn Reson Med 74:934–944, 2015. © 2014 Wiley Periodicals, Inc.